Janus membrane, preparation method and application thereof, and emulsion treatment device

By grafting a copolymer crosslinking product of tannic acid and gelatin onto one side of a PVDF membrane to form a Janus membrane, the surface fouling and pore blockage problems of PVDF membranes in treating oily wastewater are solved, thereby improving water flux and separation efficiency.

CN121648760APending Publication Date: 2026-03-13WUHAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202610001536.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-04
Publication Date
2026-03-13

AI Technical Summary

Technical Problem

Existing PVDF membranes are prone to adsorption by proteins and oil when treating oily wastewater, leading to surface contamination and pore blockage, reducing water flux and affecting oil-water separation efficiency.

Method used

Janus membranes were prepared by grafting a copolymer crosslinking product of tannic acid and gelatin onto one side of a polyvinylidene fluoride substrate, forming a side with higher hydrophilicity and another side with higher hydrophobicity. This reduced the contact angle of the hydrophilic side and decreased the adsorption of proteins and oils.

Benefits of technology

It increases water flux, enhances the filtration performance and lifespan of PVDF membranes, and achieves efficient separation of emulsions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121648760A_ABST
    Figure CN121648760A_ABST
Patent Text Reader

Abstract

The invention discloses a Janus membrane as well as a preparation method and application thereof and an emulsion treatment device, and relates to the technical field of membrane filtration, the Janus membrane comprises a polyvinylidene fluoride base membrane and a copolymerization crosslinking product grafted on the surface of one side of the polyvinylidene fluoride base membrane, the copolymerization crosslinking product comprises a product formed by tannic acid and gelatin through a Michael addition reaction. Wherein the copolymerization crosslinking product is grafted on the surface of one side of the polyvinylidene fluoride base membrane, the contact angle of the side is reduced, the contact angle of the surface of the other side of the polyvinylidene fluoride base membrane is still high, and the contact angles of the surfaces of the two sides form a difference value, so that the hydrophilicity of one side of the polyvinylidene fluoride base membrane is high, the hydrophobicity of the other side of the polyvinylidene fluoride base membrane is high, and the Janus membrane is formed. The Janus membrane is suitable for efficient separation of emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane filtration technology, and in particular to a Janus membrane, its preparation method and application, and an emulsion treatment device. Background Technology

[0002] Oily wastewater, primarily composed of water-in-oil or oil-in-water emulsions, is a complex type of water pollution that has a serious impact on the ecological environment and human health.

[0003] Polyvinylidene fluoride (PVDF) is one of the most powerful membrane materials for oil-water separation processes. It has many advantages, such as high mechanical strength, heat resistance, acid and alkali resistance, and chemical resistance.

[0004] However, when treating oily wastewater, PVDF membranes are easily adsorbed by proteins and oil, leading to surface fouling and pore blockage, which in turn reduces water flux and affects treatment efficiency. Summary of the Invention

[0005] The main objective of this invention is to propose a Janus membrane, its preparation method and application, and an emulsion treatment device, aiming to solve the problem of difficulty in separating oil and water in emulsions in the prior art.

[0006] To achieve the above objectives, the present invention proposes a Janus membrane, the Janus membrane comprising a polyvinylidene fluoride substrate and a copolymer crosslinking product grafted onto one side surface of the polyvinylidene fluoride substrate, the copolymer crosslinking product comprising a product formed by a Michael addition reaction of tannic acid and gelatin.

[0007] In one embodiment, the mass ratio of the polyvinylidene fluoride substrate to the copolymer crosslinking product is 50-5; and / or, The mass ratio of tannic acid to gelatin is 0.8 to 1.2.

[0008] In one embodiment, the polyvinylidene fluoride substrate has a first side surface and a second side surface, and the copolymer crosslinking product is grafted onto the first side surface of the polyvinylidene fluoride substrate. The contact angle A of the first side surface and the difference B between the contact angles of the second side surface; 0°<BA≤65°.

[0009] In one embodiment, the value of A ranges from 30° to 90°; and / or, The value of B ranges from 90° to 130°.

[0010] In one embodiment, the porosity of the Janus membrane is 25% to 55%; and / or, The pore size of the Janus membrane is 25~70 nm; and / or, The pure water flux of the Janus membrane is 10~40 g / (m³). 2 ·s).

[0011] The present invention also provides a method for preparing a Janus membrane, the method comprising the following steps: S1. Provide a polyvinylidene fluoride (PVDF) substrate film; S2. After wetting the polyvinylidene fluoride substrate with ethanol, it is placed in an alkaline Tris-HCl solution containing gelatin and tannic acid to carry out a modification reaction, thereby obtaining a Janus film.

[0012] In one embodiment, step S1 includes: Polyvinylidene fluoride (PVDF) substrate film was prepared by phase inversion method.

[0013] In one embodiment, in step S2: The pH of the alkaline Tris-HCl solution containing gelatin and tannic acid is 7.0–9.2; and / or, The temperature of the modification reaction is 35~45℃; and / or, The modification reaction takes 5-7 hours; and / or, In the alkaline Tris-HCl solution containing gelatin and tannic acid, the concentration of tannic acid is 1~3 g / L; and / or, The mass ratio of tannic acid to gelatin is 0.8 to 1.2.

[0014] The present invention also provides an application of Janus membrane in separating oil and water in an oil-in-water emulsion, wherein the Janus membrane includes the aforementioned Janus membrane or a Janus membrane prepared by the aforementioned method of preparing Janus membrane.

[0015] The present invention also provides an emulsion treatment apparatus, the emulsion treatment apparatus comprising the aforementioned Janus membrane or a Janus membrane prepared by the aforementioned method for preparing the Janus membrane.

[0016] In this invention, a copolymer crosslinking product is grafted onto one side of a polyvinylidene fluoride (PVDF) substrate membrane, reducing the contact angle on that side. The contact angle on the other side of the PVDF substrate membrane remains relatively high. This difference in contact angles between the two sides results in one side of the PVDF substrate membrane being more hydrophilic and the other more hydrophobic, forming a Janus membrane. The more hydrophilic side exhibits lower adsorption rates for proteins and oils, reducing surface contamination and pore blockage during filtration, increasing water flux, and enhancing the filtration performance and lifespan of the PVDF membrane. This Janus membrane is suitable for the efficient separation of emulsions. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0018] Figure 1 This is an image of the Janus-A facial mask in Embodiment 1 of the present invention; Figure 2 This is an image of the Janus-B facial mask in Embodiment 1 of the present invention; Figure 3 This is a diagram showing the contact angle test results of the Janus-A side of the Janus membrane freshly prepared in Example 1 of the present invention; Figure 4 The image shows the contact angle test results of the Janus-B side of the Janus membrane freshly prepared in Example 1 of this invention. Figure 5 This is a graph showing the contact angle test results of the Janus-A surface of the Janus membrane prepared in Example 1 of the present invention after immersion in water for 24 hours; Figure 6 The figures show the water contact angle test results of the hydrophilic surface of the Janus membrane in Examples 1-5 of this invention; Figure 7 The diagram shows the results of vacuum filtration of an oil-water mixture using the Janus membrane in Example 1, as provided by the present invention. Figure 8 The diagrams provided by this invention show the separation efficiency of oil-water mixtures filtered by Janus membranes in Examples 1-5 and the separation flux of oil-in-water emulsions filtered by these membranes.

[0019] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Oily wastewater, primarily composed of water-in-oil or oil-in-water emulsions, is a complex type of water pollution that has a serious impact on the ecological environment and human health.

[0022] Polyvinylidene fluoride (PVDF) is one of the most powerful membrane materials for oil-water separation processes. It has many advantages, such as high mechanical strength, heat resistance, acid and alkali resistance, and chemical resistance.

[0023] However, when treating oily wastewater, PVDF membranes are easily adsorbed by proteins and oil, leading to surface fouling and pore blockage, which in turn reduces water flux and affects treatment efficiency.

[0024] In view of this, the present invention provides a Janus membrane comprising a polyvinylidene fluoride substrate and a copolymer crosslinking product grafted onto one side surface of the polyvinylidene fluoride substrate, the copolymer crosslinking product comprising a product formed by a Michael addition reaction of tannic acid and gelatin.

[0025] In the technical solution of this invention, the copolymer crosslinking product is grafted onto one side of the polyvinylidene fluoride (PVDF) substrate membrane, reducing the contact angle on that side. The contact angle on the other side of the PVDF substrate membrane remains relatively high. This difference in contact angles between the two sides results in one side of the PVDF substrate membrane being more hydrophilic and the other more hydrophobic, forming a Janus membrane. The side with higher hydrophilicity exhibits lower adsorption rates for proteins and oils, reducing surface contamination and pore blockage during filtration, increasing water flux, and enhancing the filtration performance and lifespan of the PVDF membrane. This Janus membrane is suitable for the efficient separation of emulsions.

[0026] It should be noted that the copolymer crosslinking product described in this invention is formed by a Michael addition reaction between tannic acid and gelatin. Specifically, it can be formed under alkaline conditions by a Michael addition reaction between tannic acid and gelatin. Since gelatin is a protein mixture, its nucleophilic side chains (such as -NH2 of lysine, -SH of cysteine, guanidin of arginine, etc.) can participate in the addition reaction. Tannic acid is a mixed polyphenol composed of a glucose core and multiple galloyl groups (usually 5-10). Each galloyl group contains multiple phenolic hydroxyl groups and can be oxidized to ortho-quinone. The oxidized ortho-quinone will undergo a Michael addition reaction under the attack of lysine residues (containing -NH2) in gelatin as a nucleophile, forming a copolymer crosslinking product. The specific chemical formula is as follows:

[0027] It should be noted that the copolymer crosslinking product formed by the above reaction will adhere to the polyvinylidene fluoride substrate. The copolymer crosslinking product contains residual polyhydroxy groups of tannic acid and amino groups of gelatin. These hydrophilic groups effectively ensure the hydrophilicity of the membrane.

[0028] In some embodiments, the mass ratio of the polyvinylidene fluoride substrate to the copolymer crosslinking product is 50 to 5. The mass ratio can be 50, 40, 30, 20, 10, or 5. A mass ratio within the above range ensures that one side of the polyvinylidene fluoride substrate is grafted with a sufficient amount of copolymer crosslinking product and hydrophilic groups, ensuring that the contact angle of that side surface is lower and its hydrophilicity is better than that of the other side surface.

[0029] In some embodiments, the mass ratio of tannic acid to gelatin is 0.8 to 1.2. The mass ratio can be 0.8, 1, or 1.2. A mass ratio within this range ensures a high content of tannic acid grafted onto the membrane surface, a large number of hydrophilic carboxyl groups, a smaller contact angle on the grafted side of the polyvinylidene fluoride substrate, a larger membrane pore size, and a higher pure water flux.

[0030] In some embodiments, the polyvinylidene fluoride (PVDF) substrate membrane has a first side surface and a second side surface, and the copolymer crosslinking product is grafted onto the first side surface of the PVDF substrate membrane: the contact angle A of the first side surface and the difference between the contact angles B of the second side surface are: 0° < BA ≤ 65°. The difference between A and B can be 10°, 50°, 60° or 65°. A difference within the above range can ensure that the Janus membrane has good self-driving filtration properties, low requirements for external pressure, and facilitates rapid filtration and separation of emulsions under normal pressure.

[0031] In some embodiments, the value of A ranges from 30° to 90°; and / or the value of B ranges from 90° to 130°. The value of A can be 30°, 50°, 70° or 90°, and the value of B can be 90°, 110° or 130°. Both values ​​are controlled within the above ranges, and the difference between A and B is guaranteed to be within 0° to 65°. The Janus membrane has a large pure water flux and a large single processing capacity, and has a good oil-water separation effect on emulsions.

[0032] Preferably, the porosity of the Janus membrane is 25%~55%; and / or, the pore size of the pores in the Janus membrane is 25~70 nm; and / or, the pure water flux of the Janus membrane is 10~40 g / (m³). 2 The porosity of the Janus membrane can be 25%, 35%, 45%, or 55%, and the pore size can be 25 nm, 55 nm, or 70 nm. The pure water flux of the Janus membrane is 10 g / (m³). 2 ·s), 25g / (m 2 ·s) or 40g / (m 2 By controlling the porosity of the Janus membrane within the above range, it can be ensured that the Janus membrane has a good separation effect on oil and water in the emulsion and a large single processing capacity.

[0033] The present invention also provides a method for preparing a Janus membrane, the method comprising the following steps: S1, providing a polyvinylidene fluoride substrate; S2, after impregnating the polyvinylidene fluoride substrate with ethanol, placing it in an alkaline Tris-HCl solution containing gelatin and tannic acid to carry out a modification reaction to obtain a Janus membrane.

[0034] In the technical solution of this invention, the polyvinylidene fluoride (PVDF) substrate is wetted with ethanol, which reduces its surface tension. When placed in an alkaline Tris-HCl solution containing gelatin and tannic acid, the PVDF substrate floats in the solution, i.e., it is at the air-water interface, with one side of its surface in contact with water and the other side exposed to air. Under alkaline conditions, gelatin and tannic acid undergo a Michael addition reaction, thereby grafting a copolymer crosslinking product onto the water-contacting side of the PVDF substrate. As a result, only the water-contacting side is modified to reduce the contact angle of that side, while the contact angle of the other side remains high, thus forming a Janus film.

[0035] In some embodiments, step S1 includes: preparing a polyvinylidene fluoride substrate film using a phase inversion method. The phase inversion method is relatively simple to prepare.

[0036] In some embodiments, in step S2: the pH of the alkaline Tris-HCl solution containing gelatin and tannic acid is 7.0~9.2; and / or, the temperature of the modification reaction is 35~45℃; and / or, the time of the modification reaction is 5~7h; and / or, the concentration of tannic acid in the alkaline Tris-HCl solution containing gelatin and tannic acid is 1~3g / L; and / or, the mass ratio of tannic acid to gelatin is 0.8~1.2. That is, by simultaneously controlling the pH of the alkaline Tris-HCl solution containing gelatin and tannic acid, the concentration of tannic acid, the mass ratio of tannic acid to gelatin, the temperature and time of the modification reaction within the above ranges, it can be ensured that more copolymer crosslinking products are grafted onto the surface of the polyvinylidene fluoride substrate in contact with water, thereby improving hydrophilicity.

[0037] It should be noted that, compared to ordinary oil-water mixtures, separating oil and water in oil-in-water emulsions is more difficult. The specific reason for this difference in difficulty lies in the presence of emulsifiers (surfactants) in the emulsion, which can form a stable interfacial film, hindering the aggregation and coalescence of oil / water droplets. This invention also provides an application of a Janus membrane in separating oil and water in oil-in-water emulsions. The Janus membrane includes the aforementioned Janus membrane or a Janus membrane prepared by the aforementioned method. The Janus membrane provided by this invention exhibits good performance in separating oil and water in oil-in-water emulsions. Therefore, it possesses all the beneficial effects of the aforementioned Janus membrane and its preparation method, which will not be elaborated upon further here.

[0038] The present invention also provides an emulsion treatment apparatus, which includes the aforementioned Janus membrane or a Janus membrane prepared by the aforementioned method for preparing the Janus membrane. Therefore, it possesses all the beneficial effects of the aforementioned Janus membrane and the aforementioned method for preparing the Janus membrane, which will not be elaborated further here.

[0039] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0040] Example 1 A Janus membrane is prepared by the following steps: Step S1: Construction of the PVDF substrate membrane using the NIPS (Natural Inversion Phase Method): Dioctyl phthalate, PVDF powder, and 1-methyl-2-pyrrolidone (mass ratio 8:12:80) were sequentially placed into a round-bottom flask and dissolved under magnetic stirring (330 r / min, 70℃) for 7 h until a homogeneous solution was formed. The homogeneous solution was then ultrasonically cleaned for 30 min to ensure uniform dispersion, followed by standing at room temperature for 24 h to remove bubbles, yielding the casting solution. A glass rod wrapped with adhesive tape was used as a scraper to slowly pour the casting solution onto a clean and dried glass plate. The film was then scraped onto the glass plate surface using the prepared scraper. After scraping, 30 s was allowed for the solvent on the glass plate to evaporate completely. The glass plate with the film was then placed in deionized water at 25℃ until the film completely gelled and detached from the glass plate. The membrane was removed from the water and then immersed in deionized water for cleaning. It was then rinsed in anhydrous ethanol, and this process was repeated several times to remove residual organic solvents from the membrane. Finally, it was dried for later use to obtain the PVDF substrate membrane.

[0041] Step S2, Janus membrane preparation: 6.055 g of trihydroxyaminomethane was weighed and dissolved in 800 mL of deionized water in a beaker. The pH of the solution was adjusted to 8.5 using hydrochloric acid. The solution was then transferred to a 1 L volumetric flask and diluted to volume to prepare a 50 mM Tris-HCl buffer solution. The prepared base membrane was immersed in a 1:2 mixture of ethanol and deionized water and ultrasonically cleaned for 30 min to remove contaminants and impurities from the membrane surface. The PVDF membrane was removed, rinsed with distilled water, and then dried in a 30°C oven. 200 mL of the prepared Tris-HCl buffer solution was added to a clean beaker. 0.5 g of gelatin was added and stirred continuously until the gelatin was completely dissolved. Then, 0.5 g of tannic acid was added and stirred until the tannic acid was also completely dissolved, yielding a tannic acid-gelatin solution with a concentration of 2.5 g / L for both tannic acid and gelatin. The prepared tannic acid-gelatin solution was poured into a petri dish. A pre-treated PVDF membrane, moistened with ethanol, was then placed in the tannic acid-gelatin solution. Due to the hydrophobicity of the PVDF membrane, it would be positioned precisely at the air-water interface. The reaction was carried out at 40°C for 6 hours to obtain the modified Janus membrane. The modified Janus membrane was then removed with tweezers and rinsed thoroughly in deionized water and ethanol to remove any ungrafted stable substances and impurities from the membrane surface. It was then naturally dried at room temperature to obtain a Janus membrane with bi-sided wettability.

[0042] Example 2 The difference between Example 2 and Example 1 is that: In the tannic acid-gelatin solution, the concentration of tannic acid is 1 g / L and the concentration of gelatin is 1 g / L.

[0043] Example 3 The difference between Example 3 and Example 1 is that: In the tannic acid-gelatin solution, the concentration of tannic acid is 1.5 g / L and the concentration of gelatin is 1.5 g / L.

[0044] Example 4 The difference between Example 4 and Example 1 is that: In the tannic acid-gelatin solution, the concentration of tannic acid is 2 g / L and the concentration of gelatin is 2 g / L.

[0045] Example 5 The difference between Example 5 and Example 1 is as follows: In the tannic acid-gelatin solution, the concentration of tannic acid is 3 g / L and the concentration of gelatin is 3 g / L.

[0046] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: Step S2 is not performed.

[0047] Performance testing 1. The appearance of the Janus membrane prepared in Example 1 was observed by taking photographs. The side surface modified with tannic acid-gelatin was designated as Janus-A, and the side surface not modified was designated as Janus-B. The photographic results are as follows. Figure 1 and Figure 2 As shown.

[0048] Depend on Figure 1 and Figure 2 It can be seen that the surface of Janus-A mask changed from white to yellow-green after tannic acid-gelatin grafting, indicating that tannic acid was successfully grafted onto the surface of the object; while the surface of Janus-B mask remained white.

[0049] 2. The contact angles of the Janus-A and Janus-B surfaces of the Janus membrane prepared in Example 1 were measured. The Janus membrane was immersed in water for 24 hours before the contact angle of the Janus-A surface was measured. The method for measuring the contact angle is as follows: After the Janus membrane was thoroughly dried in an oven, it was cut into rectangles and fixed to a glass slide with double-sided tape. Using an OCA-25 contact angle meter, a 3 μL drop of deionized water was placed on the surface of the membrane sample. The contact angle between the droplet and the solid surface was photographed using the instrument's built-in camera. During photography, the camera must be perpendicular to the contact angle platform and on the same plane. Three membrane samples were cut and the average value was calculated, and the standard deviation was determined. The test results are shown below. Figure 3 , Figure 4 , Figure 5As shown.

[0050] Depend on Figure 3 , Figure 4 and Figure 5 It can be seen that the contact angles of the Janus-A and Janus-B sides of the freshly prepared Janus membrane are 53.4° and 98°, respectively. After soaking in water for 24 hours, the contact angle of the Janus-A side of the freshly prepared Janus membrane is 56°, which is basically unchanged compared with the water contact angle of the Janus-A side before soaking. This further illustrates that the unilateral modification of the Janus membrane by tannic acid-gelatin is successful under the conditions of 40℃ and grafting time of 6 hours.

[0051] 3. The effects of different concentrations of tannic acid and gelatin (1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L) on the water contact angle, porosity, pore size, and pure water flux of the hydrophilic surface of the Janus membrane were investigated in the tannic acid-gelatin solutions of Examples 1-5. The test methods are shown below: (1) The test method for the water contact angle is the same as shown in 2; the results are as follows: Figure 6 As shown; (2) Porosity and pore size: The area cut is 4 cm² 2 The membrane was weighed dry on an electronic balance; the membrane thickness was measured using a micrometer at three locations, and the average value was taken. The membrane was then immersed in deionized water for 12 hours, and after drying the surface, the wet membrane weight was measured. The formulas for calculating porosity and pore size are:

[0052]

[0053] Where P is the membrane porosity (%), m2 is the mass of the wet membrane (kg), m1 is the mass of the dry membrane (kg), and ρ is the density of deionized water (0.997 g / cm³). 3 A represents the surface area of ​​the membrane, in meters (m²). 2 h represents the average thickness of the membrane, in meters (m). r is the average pore size of the membrane, in nm; P is the porosity of the membrane, in % %. ρ is the viscosity of deionized water, in Pa·s; h is the average membrane thickness, in meters; Q is the volume of deionized water filtered per unit time, in cubic meters per second. 3 ·s; A is the surface area of ​​the membrane, in m² 2 △p represents the pressure during deionized water filtration, in MPa. The test results are shown in Table 1.

[0054] (3) Pure water flux: Cut the soaked ultrafiltration membrane into small round pieces and use a cup-type ultrafiltration device to measure the water flux of the composite membrane. Weigh a certain mass of deionized water at room temperature working pressure, pre-press the membrane with deionized water for a period of time until the flux stabilizes, record the mass of water permeated within a certain time at 0.2 MPa, and further calculate the water flux according to the following formula. Take the average value of the three measurements and calculate the standard deviation.

[0055] Pure water flux

[0056] In the formula, J is the pure water flux of the membrane at a pressure of 0.2 MPa, and the unit is g / (m³). 2 ·s); m is the mass of liquid passing through in time t, in grams; s is the effective measurement area of ​​the membrane, in m². 2 t represents the measurement time in seconds. The test results are shown in Table 1.

[0057] Depend on Figure 6 It can be seen that, within the same grafting time range, the contact angle of the Janus-A surface showed a trend of first decreasing, then slightly increasing, and finally stabilizing with the increase of tannic acid and gelatin concentrations. Specifically, the water contact angle of the Janus-A surface decreased from 98°±2° to 38°±1° and finally stabilized at around 43°±2°. The contact angle was smallest at a tannic acid concentration of 2 g / L, and after significance analysis, the P value was <0.05, indicating that the tannic acid concentration has an impact on the contact angle. Finally, the contact angle of the modified Janus-A hydrophilic surface was lower than that of the unmodified PVDF base film. This is because the reaction of tannic acid and gelatin grafted a large number of hydrophilic groups onto the film surface, gradually increasing the hydrophilicity of the originally hydrophobic film surface. After modification to a certain extent, the water contact angle tended to stabilize and no longer decreased with increasing concentration. This is because the tannic acid fully reacted on the film surface, giving the film its maximum hydrophilicity.

[0058] Table 1. Effects of different concentrations of tannic acid on the porosity, average pore size, and pure water flux of Janus membranes.

[0059] Table 1 shows that the pore size, porosity, and pure water flux of the Janus membrane first increase and then decrease with the concentration of grafted tannic acid-gelatin. At 2.5 g / L, the pore size reaches its maximum of 65.32 nm, the porosity is 53.99%, and the pure water flux reaches 38.66 ± 1.99 g / (m³). 2This is because tannic acid and gelatin undergo a Michael addition reaction on the membrane surface, grafting hydrophilic groups such as hydroxyl and amino groups onto the membrane surface. This alters the chemical morphology of the membrane surface, resulting in a macroporous structure and increased porosity and water flux of the Janus membrane. When the tannic acid concentration is low, the amount of tannic acid grafted onto the membrane surface is small, resulting in few hydrophilic carboxyl groups and fewer chemical groups capable of undergoing Michael addition reactions with the amino groups of gelatin. Consequently, the number of introduced hydrophilic groups is also limited, leading to a larger water contact angle, smaller membrane pore size, and lower pure water flux. As the tannic acid-gelatin concentration increases, the performance of the modified Janus membrane gradually improves. The water contact angle of the hydrophilic side gradually decreases, the difference between the hydrophilic and hydrophobic sides increases, and the number of introduced hydrophilic groups gradually increases. The porosity is maximized at 2.5 g / L, leading to a gradual increase in the pure water flux of the Janus membrane. When the concentration exceeds 2.5 g / L, excessive accumulation causes tannic acid-gelatin to deposit on the membrane surface, increasing the membrane thickness and even causing blockage. This reduces the membrane porosity and water flux.

[0060] 4. Using the Janus membranes described in Examples 1-5, the oil-water mixtures and emulsions were tested for oil-water phase separation. Corn oil was selected as the model oil. The specific methods for preparing the oil-water mixtures and emulsions are shown below (the methylene blue solution used was 5 mg / L): (1) Preparation of oil-water mixture: Deionized water was stained with methylene blue and then mixed with corn oil in a volume ratio of 1:1 to deionized water to obtain oil-water mixture.

[0061] (2) Preparation of oil-in-water emulsion: 0.5 g of sodium dodecyl sulfate and 1 mL of corn oil were added to 99 mL of the prepared methylene blue solution and stirred for 4 hours at 800 r / min to obtain a corn oil-in-water emulsion. The emulsion was allowed to stand for 6 hours without separation before being used for subsequent experimental research.

[0062] Oil-water separation experiment: The oil-water separation device was a vacuum filtration device, and the oil-water mixture was added from the Buchner funnel at the top. The specific operation process is as follows: The prepared Janus membrane was placed in the Buchner funnel, the prepared oil-water mixture or emulsion was poured in, and the circulating water vacuum pump was turned on for filtration at a pressure of 0.08 MPa. After separation, the separated liquid was collected, and the separation flux J and oil-water separation efficiency R were calculated.

[0063]

[0064] ×100% In the formula, J is the separation flux, with units of g / m³. 2 •s; m is the mass of liquid passing through in time t, in grams; s is the effective measurement area of ​​the membrane, in m².2 t represents the measurement time, measured in seconds. In the formula, R is the oil-water separation efficiency, in %; m0 is the mass of the solution before separation, in g; and m1 is the mass of the solution after separation, in g.

[0065] Test results are as follows Figure 7 and Figure 8 As shown.

[0066] Depend on Figure 7 It is known that when using the Janus-A surface to separate oil-water mixtures, the yellow oil layer is on top and the blue water layer is at the bottom due to density differences. However, experiments showed that when using the PVDF-based membrane (Comparative Example 1) to separate light oil-water mixtures, both water and oil could permeate through the membrane under a pressure of 0.08 MPa, failing to achieve oil-water separation. This is because the PVDF membrane itself is an oleophilic and hydrophobic material, allowing oil to pass through. In contrast, the Janus membrane modified with tannic acid and gelatin, due to the strong hydrophilicity of its Janus-A surface, allows water molecules to easily pass through while blocking corn oil at the top.

[0067] Depend on Figure 8 It can be seen that the separation efficiency of the Janus membrane for oil-water mixtures initially increases and then decreases with increasing tannic acid-gelatin concentration, with the separation efficiency consistently exceeding 80%, reaching a maximum of 95.38% at a concentration of 2 g / L. At 2 g / L, the grafting effect of tannic acid-gelatin on the membrane surface is optimal, with the largest contact angle difference and wetting difference between the two sides, resulting in the best separation effect for oil-water mixtures. The separation efficiency decreases with increasing tannic acid-gelatin concentration, possibly because the reaction of tannic acid and gelatin on the membrane surface affects the membrane morphology, worsening the wetting difference between the two sides and reducing the Janus membrane's oil-blocking effect, thus lowering the separation efficiency.

[0068] Furthermore, the separation flux of the Janus membrane for oil-in-water emulsion initially increased and then decreased, reaching a maximum of 4.89 g / (m²) at 2.5 g / L. 2 At 2.5 g / L, the water contact angle of the Janus membrane tends to stabilize, and the porosity is at its maximum, resulting in a larger pure water flux and an increased oil-in-water separation flux. At 3 g / L, the water contact angle decreases, the pore size and porosity decrease, and the oil-in-water separation flux decreases accordingly.

[0069] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A Janus membrane, characterized in that, The Janus membrane comprises a polyvinylidene fluoride substrate and a copolymer crosslinking product grafted onto one side of the polyvinylidene fluoride substrate, the copolymer crosslinking product comprising a product formed by a Michael addition reaction of tannic acid and gelatin.

2. The Janus membrane as described in claim 1, characterized in that, The mass ratio of the polyvinylidene fluoride substrate to the copolymer crosslinking product is 50-5; and / or, The mass ratio of tannic acid to gelatin is 0.8 to 1.

2.

3. The Janus membrane as described in claim 1, characterized in that, The polyvinylidene fluoride substrate has a first side surface and a second side surface, and the copolymer crosslinking product is grafted onto the first side surface of the polyvinylidene fluoride substrate: The contact angle A of the first side surface and the difference B between the contact angles of the second side surface; 0°<BA≤65°.

4. The Janus membrane as described in claim 3, characterized in that, The value of A ranges from 30° to 90°; and / or, The value of B ranges from 90° to 130°.

5. The Janus membrane as described in claim 1, characterized in that, The porosity of the Janus membrane is 25%~55%; and / or, The pore size of the Janus membrane is 25~70 nm; and / or, The pure water flux of the Janus membrane is 10~40 g / (m³). 2 ·s).

6. A method for preparing a Janus membrane as described in any one of claims 1 to 5, characterized in that, The method for preparing the Janus membrane includes the following steps: S1. Provide a polyvinylidene fluoride (PVDF) substrate film; S2. After wetting the polyvinylidene fluoride substrate with ethanol, it is placed in an alkaline Tris-HCl solution containing gelatin and tannic acid to carry out a modification reaction, thereby obtaining a Janus film.

7. The method for preparing the Janus membrane as described in claim 6, characterized in that, Step S1 includes: Polyvinylidene fluoride (PVDF) substrate film was prepared by phase inversion method.

8. The method for preparing the Janus membrane as described in claim 6, characterized in that, In step S2: The pH of the alkaline Tris-HCl solution containing gelatin and tannic acid is 7.0–9.2; and / or, The temperature of the modification reaction is 35~45℃; and / or, The modification reaction takes 5-7 hours; and / or, In the alkaline Tris-HCl solution containing gelatin and tannic acid, the concentration of tannic acid is 1~3 g / mL; and / or, The mass ratio of tannic acid to gelatin is 0.8 to 1.

2.

9. An application of a Janus membrane in separating oil and water in an oil-in-water emulsion, characterized in that, The Janus membrane includes the Janus membrane as described in any one of claims 1 to 5 or the Janus membrane prepared by the method described in any one of claims 6 to 8.

10. An emulsion processing apparatus, characterized in that, The emulsion treatment apparatus includes a Janus membrane prepared by any one of claims 1 to 5 or by any one of claims 6 to 8.

Citation Information

Cited By

  • Layer-by-layer deposition modified ultrafiltration membrane with anti-pollution and antibacterial performance, and preparation method and application thereof

    CN122124644A